Vegetation dynamics during the early to mid-Holocene transition in NW Malta, human impact versus climatic forcing - Djamali, Morteza; Gambin, Belinda; Marriner, Nick; Andrieu-Ponel, Valérie; Gambin, Timmy; Gandouin, Emmanuel; Lanfranco, Sandro; Médail, Frédéric; Pavon, Daniel; Ponel, Philippe; Morhange, Christophe (Vegetation History and Archaeobotany, 2012)
A pollen diagram was constructed for the earlyto mid-Holocene transition (ca. 7350–5600 cal. B.P./5400– 3650 B.C.) from the Burmarrad ria located in NW Malta. The vegetation at ca. 7350–6960 cal. B.P./5400–5010 B.C. was characterized by an almost tree-less steppe-like open landscape. Early Holocene dry climatic conditions were most probably due to intensiﬁcation of the subtropical monsoon circulation that strengthened the subtropical anticyclonic descent over the central Mediterranean and blocked the penetration of humid air masses from the North Atlantic Ocean. At ca. 6950 cal. B.P./5000 B.C., the steppe-like vegetation was suddenly replaced by a Mediterranean evergreen forest or dense scrub dominated by Pistacia cf. lentiscus trees. This event, which has simultaneously been recorded in southern Sicily, was most probably caused by the southward shift of the ITCZ permitting the eastward movement of the North Atlantic cyclonic systems. Traces of human activities are evident in the pollen diagram since the beginning of the record but become more pronounced from the onset of the Temple Cultural Phase at ca. 6050 cal. B.P./4100 B.C. with a gradual decline of tree pollen. We suggest that the early- to mid-Holocene vegetation transformation was mainly controlled by a regional climatic change that occurred in a landscape only slightly impacted by human activities.
Keywords: Evergreen Pistacia; Mediterranean; Monsoon intensiﬁcation; Neolithic; Pollen analysis; Temple cultural phase